Penatalaksanaan Fisioterapi pada Kasus Patellafemoral Pain Syndrome dengan Modalitas Kinesio Tapping dan Kinetic Chain Exercise - Mary Zahra Srimela; Putra Hadi; Faridah Faridah (3031-8572, 2022)
Patellofemoral pain syndrome is an articular disorder caused by pain in the anterior part of the knee, which usually occurs in physically active people aged 40 years and under, causing pain, functional deficits, and muscle weakness. Pain in the anterior knee, one of which is due to changes in the knee structure from poor posture in daily life. This study aims to determine the management of physiotherapy in the condition of Patellofemoral pain syndrome by using Kinesio tapping and kinetic chain exercise modalities that can reduce pain, increase muscle strength and increase functional activity. The method used is a case study method with one respondent. The results of research conducted, for six times therapy in two weeks can reduce pain, increase muscle strength and increase functional activity, in patients with Patellofemoral pain syndrome. The conclusion of this study is that Kinesio tapping and kinetic chain exercise can reduce pain, increase muscle strength and increase functional activity.